Quando lo ‘scandalo’ diventa provocazione: Il postsecolare e il teatro iconoclasta di Romeo Castellucci - Jansen, Monica (Incontri. Rivista europea di studi italiani, 2020)
When ‘scandal’ becomes provocation The postsecular and Romeo Castellucci’s theatre of iconoclasm Romeo Castellucci’s performance On the Concept of the Face Regarding the Son of God has led to a series of violent protests coordinated by Catholic groups in France (Paris 2011, Le Mans 2018) and Italy (Milan 2012) and has been judged as being blasphemous and ‘Christianophobic’. Castellucci in the media has defended his piece using biblical terms and advocating his artistic right to create ‘scandal’. This contribution intends to investigate the limits between provocation and ‘scandal’ with the help of a work of art that adoperates consciously an ‘iconoclash’ (Latour 2002) montage between avant-garde transgression and the symbolic code of Catholicism. While the freedom of artistic expression enjoys the protection of the state, this ‘natural’ right is put into question by the postsecular ‘return of religion’ in the public sphere (Habermas 2006). The analysis of the Catholic protests against Castellucci’s piece and the director’s aesthetic and ethical goals, both show how the configuration of postsecular art becomes part of the ‘denaturalization’ of secular and religious normativity in postsecular society (Parmaksız 2018).